2012
DOI: 10.1021/jf2053959
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulating the Human Intestinal Microbiome Using Whole Plant Foods, Polyphenols, and/or Fiber

Abstract: Whole plant foods, including fruit, vegetables, and whole grain cereals, protect against chronic human diseases such as heart disease and cancer, with fiber and polyphenols thought to contribute significantly. These bioactive food components interact with the gut microbiota, with gut bacteria modifying polyphenol bioavailability and activity, and with fiber, constituting the main energy source for colonic fermentation. This paper discusses the consequences of increasing the consumption of whole plant foods on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
186
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(195 citation statements)
references
References 47 publications
1
186
0
Order By: Relevance
“…Indeed, animal studies show that dried plums and/or their polyphenol-rich extracts can beneficially affect both BMD and bone biomarkers. The animal and cell studies presented in this comprehensive review are consistent with and supportive of the theory that a diet high in phenolics and/or flavonoids may enhance bone formation and 74 …”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Indeed, animal studies show that dried plums and/or their polyphenol-rich extracts can beneficially affect both BMD and bone biomarkers. The animal and cell studies presented in this comprehensive review are consistent with and supportive of the theory that a diet high in phenolics and/or flavonoids may enhance bone formation and 74 …”
Section: Discussionsupporting
confidence: 76%
“…Several human clinical studies showed that various HP tuber extracts (equivalent to 50-60 mg harpagoside daily, administered for a variable period between 8 and 16 weeks, depending on the study) significantly improved the clinical picture of subjects with knee and hip osteoarthritis in terms of pain, movement limitation, and joint crepitus [72][73][74]. The severity of pain and other symptoms was assessed by the WOMAC questionnaire, VAS, Lequesne Index, physician exam and/or pain-relieving medication dose.…”
Section: Harpagophytum Procumbens Fam Pedaliaceaementioning
confidence: 99%
“…They are also known to have antibacterial effects, anti-inflammatory activities and detoxification ability [31]. The TPC of the varieties analysed showed higher levels in the freeze dried 'California' variety at 427.06mgGAE/100g, 'Draper' variety at 287.96 mgGAE/100g followed by the 'Duke' variety at 262.98mgGAE/100g and the Brigatta variety at 241.41mgGAE/100g.…”
Section: Resultsmentioning
confidence: 96%
“…Fibre is an essential component of the human diet, promoting beneficial intestinal bacteria (Tuohy et al 2012). Preservation of such microbes has, in turn, been associated with decreased risk of bowel cancer and other health benefits (Kendall et al 2010).…”
Section: Qualitymentioning
confidence: 99%